Narratives of note studies of popular forms in the twentieth century - Reyes, Soledad s. (Manila University of Santo Tomas Publishing House, 2012)
Narrative of note is a collection of critical essays written between 2006-2010. The anthology includes studies on such genres as the Tagalog novel and the komiks; on the powerful institution, Liwayway magazines;and on the dominanr critical approaches in contemporary criticism as deployed by a number of Filipino critics.
Aspects of the "Medieval Vision" in selected Tagalog novels -- Beyond Madonna and Magdalena: the variety of female characters in selected popular texts -- The novel (2008) and its context -- Amorsolo and Pineda: the barrio in painting and literature (1909-1947) -- francisco V. Coching: framing the writer, the komiks, the novel -- Paano ba ang maging Bayani?: ang ginto sa Makiling (1947) sa ika -21 dantaon -- The komiks and retelling the lore of the folk -- Ang realismo sa panitikan at kulturang popular -- Ang Liwayway at ang panitikang Tagalog (1922-1975) -- The Interconnectedness of things: the production of arts in the Philippines.
Includes bibliography (pages 250-259) and index.
Keywords: Philippine literature (English) -- History and criticism; Philippine essays (English) -- Collections; Philippine novel (English) -- History and criticism